2009
DOI: 10.1053/j.ajkd.2008.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Q121 Variant of ENPP1 Gene With Decreased Kidney Function Among Patients With Type 2 Diabetes

Abstract: Background-Insulin resistance plays a role in diabetic kidney complications. The ectonucleotide pyrophosphatase/phosphodiesterase (ENPP1) (rs1044498) K121Q polymorphism has been associated with insulin resistance and related vascular complications among patients with type 2 diabetes (T2D), in many although not all studies. This study investigated whether the ENPP1 Q121 variant modulates the risk of reduced GFR in T2D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…Different characteristics of the two reference hospitals may have resulted in genetic heterogeneity, which has been excluded by estimating Cochran's Q test for no heterogeneity. Due to a lack of heterogeneity, we were able to pool data from the two study cohorts and thereby considerably increase the statistical power of the analysis (De Cosmo et al, 2009). Furthermore, the hospital-setting for recruitment used in our study could be prone to selection bias, known as Berkson's bias (Roberts et al, 1978), so that the observed prevalence and distribution of T2D may not be extrapolated to the entire population.…”
Section: Tablementioning
confidence: 99%
“…Different characteristics of the two reference hospitals may have resulted in genetic heterogeneity, which has been excluded by estimating Cochran's Q test for no heterogeneity. Due to a lack of heterogeneity, we were able to pool data from the two study cohorts and thereby considerably increase the statistical power of the analysis (De Cosmo et al, 2009). Furthermore, the hospital-setting for recruitment used in our study could be prone to selection bias, known as Berkson's bias (Roberts et al, 1978), so that the observed prevalence and distribution of T2D may not be extrapolated to the entire population.…”
Section: Tablementioning
confidence: 99%
“…A substantial interaction has been reported between the K121Q polymorphism of ENPP1 and BMI (the genetic effect has been almost exclusively observed among obese individuals) in determining insulin sensi tivity, 64,65,68 athero sclerosis 69,70 and, most importantly, T2DM. 71−73 We have also assessed whether interactions between genetic factors and BMI affect the risk of T2DM in a large sample of 5,410 individuals who participated in the GENIUS Consortium (v. Trischitta, personal communication).…”
Section: Insulin Signaling Genes and T2dmmentioning
confidence: 99%
“…By contrast, among obese individuals who carry the Q121 variant, the deleterious effect of insulin sensi tivity is no longer counterbalanced by its positive effect on BMI and insulin resistance develops, 64,65,68 which increases the risk of related abnormalities, including athero sclerosis and cardiovascular events. 69,70 In addition, under these circumstances, hyper insulinemia (which is needed to compensate for insulin resistance) is not achievable because of the deleterious effect of the Q121 variant on insulin secretion, 64 which increases the risk for overt T2DM. 71-73 overall, two independent mechanisms might explain the observed interaction between genetic factors and obesity: one is related to the protective effect of the Q121 variant against obesity, which makes the associ ation weaker in the absence of a nonobesogenic background; the other is related to the variant's deleterious effect on insulin secretion (defective insulin secretion is unable to counteract a high degree of insulin resistance owing to the coexistence of the Q121 variant and obesity), which increases the likelihood of the association with T2DM among obese individuals.…”
Section: Insulin Signaling Genes and T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, De Cosmo and cols. (52), studying patients with type 2 DM from Gargano and Padua (Italy), and from Boston (USA), demonstrated that Q allele carriers from Gar gano and Boston presented a greater risk of having a lower GFR (OR = 1.69; CI 95%: 1.1 2.6 and OR = 1.50; CI 95%: 1.0 2.2; respectively) than noncarriers. In the Padua population, results obtained showed the same trend, but did not reach formal statistical signifi cance (OR = 1.77; CI 95%: 0.7 4.5).…”
Section: Role Of Enpp1 In Diabetic Nephropathymentioning
confidence: 99%